KOMPOSISI KIMIA MINYAKASTIRI PALA WEGIO {Myristica fatua Houtt.) - Jamal, Yuliasri; Agusta, Andria (BERITA BIOLOGI, 2004)
Aril and seeds of "pala wegio" {Myristica fatua Houtt),as one of endemic plants from Moluccas, contained 0.81% and 0.73%essential oils respectively.Gas Chromatography & Mass Spectrometry (GCMS) analyses indicated two similar major components (>10%) in aril and seeds essential oils of "pala wegio", (-) a-Copaene (aril 36.11% & seeds 29.81%) and caryophyllene (aril 18.05% & seeds 34.62%).However, the seeds essential oil had the third major component unindentified with 17.58% content.